Key parameters for enhancing the thermoelectric power factor of PEDOT:PSS/PANI-CSA multilayer thin films. Issue 21 (12th April 2019) - Lee, Hyung Myung; Anoop, Gopinathan; Lee, Hye Jeong; Kim, Wan Sik; Jo, Ji Young
Abstract : The key factors that control the thermoelectric (TE) properties of PEDOT:PSS/PANI-CSA multilayer thin films to enhance the TE power factor. Abstract : Among the conducting polymers, poly(3, 4-ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS) has been extensively investigated for organic thermoelectric device applications owing to its high electrical conductivity ( σ ), flexibility and easy processability. The thermoelectric (TE) power factor – a factor that determines the efficiency of a thermoelectric material, is very critical in developing high-efficiency thermoelectric devices. The TE power factor of PEDOT:PSS requires further enhancement in realizing efficient organic TE devices. Recently, we have reported a layer-by-layer deposition technique to deposit PEDOT:PSS and poly aniline-camphor sulfonic acid (PANI-CSA) forming a PEDOT:PSS/PANI-CSA multilayer (ML) thin film structure with an enhanced thermoelectric power factor up to 49 μW m −1 K −1 . However, there exist several ambiguities regarding the parameters that control the TE power factor in (ML) thin films. In order to identify the parameters that control the TE power factor of ML thin films, PEDOT:PSS/PANI-CSA ML thin films have been deposited by varying the deposition conditions such as spin speed, the number of layers, solvent treatment, and thickness of each layer. A thermoelectric power factor up to 325 μW m −1 K −1 is achieved by properly optimizing the spin speed, number of layers, and the thickness of each layer in ML thin films. The enhanced thermoelectric power factor is the result of multiple factors such as stretching of PEDOT chains, structural conformation change from benzoid to quinoid, and excess PSS removal from the top of the PEDOT:PSS layer through solvent treatment and at the PEDOT:PSS/PANI-CSA interface. Our study provides the basis for realizing an enhanced thermoelectric power factor of organic thermoelectric multilayer structures consisting of ultra-thin polymer thin films similar to inorganic superlattices having 2D confinement.